IN THE BLOOD AND LIVER OF RATS POISENED BY SPECTACLED SNAKE VENOM - Shirinova Inobat; Mamasalimov Mukhammadjon (Galaxy International Interdisciplinary Research Journal, 2022)
It is known that catacin has high fighting properities. Previous experiments have shown that antihypoxants such as gutimine and sodium oxybutyrate give positive results after both prophylaxis and snake venom poisoning.The direct effects of catacin on tissue when poisoned by snake venom re currently poorly understood. Membrane phospholipids, which can liquefy the body , play an important role in the exchange of membrane properties.In our following studies, we aimed to monitor the results of various indicators of phospholipids in rat blood and liver catacin use and non-use after intoxitation with Central Asian spectacle snake venom.